2021
DOI: 10.3389/fchem.2021.736788
|View full text |Cite
|
Sign up to set email alerts
|

Protein Targets of Acetaminophen Covalent Binding in Rat and Mouse Liver Studied by LC-MS/MS

Abstract: Acetaminophen (APAP) is a mild analgesic and antipyretic used commonly worldwide. Although considered a safe and effective over-the-counter medication, it is also the leading cause of drug-induced acute liver failure. Its hepatotoxicity has been linked to the covalent binding of its reactive metabolite, N-acetyl p-benzoquinone imine (NAPQI), to proteins. The aim of this study was to identify APAP-protein targets in both rat and mouse liver, and to compare the results from both species, using bottom-up proteomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…Mitochondrial proteins undergo nuclear translocation, which results in cell death and nuclear DNA fragmentation. In the current research, Ginsenoside Rc was shown to significantly reduce the level of NAPQI (Geib et al, 2021). Low levels of NAPQI promote the alleviation of liver cell apoptosis, oxidative stress, and the inflammatory response.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Mitochondrial proteins undergo nuclear translocation, which results in cell death and nuclear DNA fragmentation. In the current research, Ginsenoside Rc was shown to significantly reduce the level of NAPQI (Geib et al, 2021). Low levels of NAPQI promote the alleviation of liver cell apoptosis, oxidative stress, and the inflammatory response.…”
Section: Discussionmentioning
confidence: 64%
“…Mitochondrial protein, the key target of NAPQI, appears with excess APAP (Geib et al, 2021). Studies have shown that APAP can cause oxidative stress in the mitochondria and produce ROS through the percolation of electrons from the transport chain (Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…169 Using shotgun proteomics with DDA high-resolution MS, APAP covalently modified proteins in rat and mouse livers were detected in highly complex samples. 170 The DDA is the mainstream mode for low-abundance DMPC detection. However, because of the characteristics of the DDA scanning mode, the combination of dynamic exclusion and DDA-based methods still cannot provide full coverage of peptides in complex proteomics samples, resulting in some low-abundance DMPCs that cannot be selected for fragmentation for MS analysis.…”
Section: Mass Spectrometric Analysismentioning
confidence: 99%
“…An additional dynamic exclusion technique greatly reduces redundant peptide precursor selection, extends the dynamic range, and maximizes proteome coverage of detection in shotgun proteomics 169 . Using shotgun proteomics with DDA high‐resolution MS, APAP covalently modified proteins in rat and mouse livers were detected in highly complex samples 170 . The DDA is the mainstream mode for low‐abundance DMPC detection.…”
Section: Shotgun Proteomics Aim At Dmpc Detection Strategiesmentioning
confidence: 99%